2001
DOI: 10.1590/s0004-282x2001000500024
|View full text |Cite
|
Sign up to set email alerts
|

Reversible posterior leucoencephalopathy syndrome associated with bone marrow transplantation

Abstract: -Reversible posterior leucoencephalopathy syndrome (RPLS) has previously been described in patients who have renal insufficiency, eclampsia, hypertensive encephalopathy and patients receiving immunosuppressive therapy. The mechanism by which immunosuppressive agents can cause this syndrome is not clear, but it is probably related with cytotoxic effects of these agents on the vascular endothelium. We report eight patients who received cyclosporine A (CSA) after allogeneic bone marrow transplantation or as treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Under most circumstances, the neurological symptoms and signs associated with cyclosporine use are reversible when the drug's administered dosage is decreased or it is withdrawn altogether, but symptoms may recur when the drug is reintroduced. Although neurotoxicity would appear to be more frequent when blood cyclosporine levels are substantially elevated, neurotoxicity may also occur when the drug is administered within the normal therapeutic range [4,10]. In our patient's case, his blood cyclosporine level during therapy (437 ng/ml) was only marginally above the recommended normal range (200-400 ng/ml) [10].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Under most circumstances, the neurological symptoms and signs associated with cyclosporine use are reversible when the drug's administered dosage is decreased or it is withdrawn altogether, but symptoms may recur when the drug is reintroduced. Although neurotoxicity would appear to be more frequent when blood cyclosporine levels are substantially elevated, neurotoxicity may also occur when the drug is administered within the normal therapeutic range [4,10]. In our patient's case, his blood cyclosporine level during therapy (437 ng/ml) was only marginally above the recommended normal range (200-400 ng/ml) [10].…”
Section: Discussionmentioning
confidence: 56%
“…Regions of vasodilatation and vasoconstriction tend to develop for individuals afflicted with PRES, especially in arterial boundary zones, this leading to some breakdown of the blood-brain barrier with focal transudation of fluid and petechial hemorrhages [4]. An alternative mechanism of PRES also implicates endothelial dysfunction, such a notion underpinning the treatment of affected individuals with immunosuppressive therapy, mainly cyclosporine [4,10]. It would seem likely that PRES acts by way of imparting direct toxicity on to the vascular endothelium, vasoconstriction being caused by elaboration of endothelin, similar to the appearance of microthrombosis, as in the hemolytic-uremic syndrome [4].…”
Section: Discussionmentioning
confidence: 99%
“…This patient had clinical findings and white matter alterations as reported in CSA-associated central neurotoxicity [2][3][4]. However, MRI revealed extensive leukoencephalopathy without restriction to the parieto-occipital brain areas and thus did not match the definition of a posterior leukoencephalopathy syndrome, a radiographically defined variant of leukoencephalopathy which is considered reversible after withdrawal or dose reduction of CSA [5]. This case is remarkable with respect to its refractoriness to dose reduction and withdrawal of CSA and its rapid clinical course with subsequent fatal outcome.…”
Section: Discussionmentioning
confidence: 86%
“…Teive et al (14) reported eight cases of RPLS associated with bone marrow transplantation. The patients were treated with cyclosporine A following an allogeneic bone marrow transplantation or to treat severe aplastic anemia.…”
Section: Discussionmentioning
confidence: 99%